The Routledge handbook of people and place in the 21st century city - Bishop, Kate; Marshall, Nancy (Routledge, 2020)
Increasing urbanization and increasing urban density put enormous pressure on the relationships between people and place in cities. Built environment professionals must pay attention to the impact of people-place relationships in small- to large-scale urban initiatives. A small playground in a neighborhood pocket park is an example of a small-scale urban development; a national environmental policy that influences energy sources is an example of a large-scale initiative. All scales of decision-making have implications for the people-place relationships present in cities. This book presents new research in contemporary, interdisciplinary urban challenges, and opportunities, and aims to keep the people-place relationship debate in focus in the policies and practices of built environment professionals and city managers. Most urban planning and design decisions, even those on a small scale, will remain in the urban built form for many decades, conditioning people's experience of their city. It is important that these decisions are made using the best available knowledge. This book contains an interdisciplinary discussion of contemporary urban movements and issues influencing the relationship between people and place in urban environments around the world which have major implications for both the processes and products of urban planning, design, and management. The main purpose of the book is to consolidate contemporary thinking among experts from a range of disciplines including anthropology, environmental psychology, cultural geography, urban design and planning, architecture and landscape architecture, and the arts, on how to conceptualize and promote healthy people and place relationships in the 21st-century city. Within each of the chapters, the authors focus on their specific areas of expertise which enable readers to understand key issues for urban environments, urban populations, and the links between them